Alginate-Based Materials Loaded with Nanoparticles in Wound Healing - Anna Froelich; Emilia Jakubowska; Monika Wojtyłko; Barbara Jadach; Michał Gackowski; Piotr Gadziński; Olga Napierała; Yulia Ravliv; Tomasz Osmałek (MDPI AG, 2023)
Alginate is a naturally derived polysaccharide widely applied in drug delivery, as well as regenerative medicine, tissue engineering and wound care. Due to its excellent biocompatibility, low toxicity, and the ability to absorb a high amount of exudate, it is widely used in modern wound dressings. Numerous studies indicate that alginate applied in wound care can be enhanced with the incorporation of nanoparticles, revealing additional properties beneficial in the healing process. Among the most extensively explored materials, composite dressings with alginate loaded with antimicrobial inorganic nanoparticles can be mentioned. However, other types of nanoparticles with antibiotics, growth factors, and other active ingredients are also investigated. This review article focuses on the most recent findings regarding novel alginate-based materials loaded with nanoparticles and their applicability as wound dressings, with special attention paid to the materials of potential use in the treatment of chronic wounds.